2012
DOI: 10.1038/tp.2012.94
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety- rather than depression-like behavior is associated with adult neurogenesis in a female mouse model of higher trait anxiety- and comorbid depression-like behavior

Abstract: Adult neurogenesis has been implicated in affective disorders and the action of antidepressants (ADs) although the functional significance of this association is still unclear. The use of animal models closely mimicking human comorbid affective and anxiety disorders seen in the majority of patients should provide relevant novel information. Here, we used a unique genetic mouse model displaying higher trait anxiety (HAB) and comorbid depression-like behavior. We demonstrate that HABs have a lower rate of hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 110 publications
(150 reference statements)
5
62
0
Order By: Relevance
“…They are usually compared to mice displaying normal anxiety behaviour (NAB mice). A first study reported that chronic fluoxetine was able to alleviate the depressive-like features in HAB mice but had no effects on the anxiety behaviours and on hippocampal neurogenesis (Sah et al 2012), while a second study from the same group reported that HAB mice responded normally to chronic noradrenergic drugs such as reboxetine or desipramine but were resistant to the effects of chronic SSRIs including fluoxetine, paroxetine and citalopram (Schmuckermair et al 2013). However, HAB mice did respond to repeated DBS of the nucleus accumbens (Schmuckermair et al 2013).…”
Section: Personality Factorsmentioning
confidence: 97%
“…They are usually compared to mice displaying normal anxiety behaviour (NAB mice). A first study reported that chronic fluoxetine was able to alleviate the depressive-like features in HAB mice but had no effects on the anxiety behaviours and on hippocampal neurogenesis (Sah et al 2012), while a second study from the same group reported that HAB mice responded normally to chronic noradrenergic drugs such as reboxetine or desipramine but were resistant to the effects of chronic SSRIs including fluoxetine, paroxetine and citalopram (Schmuckermair et al 2013). However, HAB mice did respond to repeated DBS of the nucleus accumbens (Schmuckermair et al 2013).…”
Section: Personality Factorsmentioning
confidence: 97%
“…The sucrose preference test was conducted based on the modification of a previously published study [47]. During this test, mice were given a free choice between two bottles, one with an escalating dose of 0.5%-1% sucrose and another with tap water.…”
Section: Sucrose Preference Testmentioning
confidence: 99%
“…We conducted the sucrose preference test, to evaluate anhedonia which is a recognised feature of human depression [47]. The animal´s preference in drinking sweet sucrose containing water compared to plain drinking water was measured over a five week-period with increasing sucrose concentrations (0.5%, 0.6%, 0.75% and 1%).…”
Section: Impaired Cognition In the Object Location Memory Task In Cavmentioning
confidence: 99%
“…Owing to selective inbreeding for the high anxiety traits for ∼ 45 generations, the HAB phenotype is extremely robust and barely amenable to any kind of pharmacological manipulation (Landgraf et al, 2007). Intriguingly, HAB mice, which largely remain unresponsive to chronic treatment with conventional anxiolytics or widely used non-specific antioxidants (Sah et al, 2012), responded to MitoQ that specifically targets mitochondria. At the molecular level, MitoQ treatment resulted in altered levels of sarcosine, AMP, and ascorbic acid in the HAB hippocampus.…”
Section: Discussionmentioning
confidence: 99%